Research progress of macrophage ferroptosis in inflammatory bowel disease and inflammation-cancer transformation - Chen, Siyu; Ma, Jing; Tang, Junling; Yang, Yang; Zhou, Shiwen; Feng, Peimin (Frontiers in Immunology, 2025)
The pathophysiology of inflammatory bowel disease (IBD), a chronic intestinal inflammatory disease, is tightly associated with immunological dysregulation, intestinal flora abnormalities, and intestinal epithelial cell destruction. Ferroptosis—a non-apoptotic cell death form that differs from the standard apoptotic mode—plays a significant regulatory role in the development of IBD through iron-dependent lipid peroxide accumulation. Iron serves as a critical component for maintaining the normal function of macrophages. Macrophages have been demonstrated to play multifaceted roles in the pathogenesis and progression of inflammatory bowel disease. The iron metabolism within macrophages may potentially influence the development of IBD and colitis-associated cancer. This paper summarizes the present research on ferroptosis and macrophages and their related molecular mechanisms. It also discusses the interactive function of macrophage ferroptosis in the development of IBD and inflammatory-cancer transformation. The development of new theoretical foundations and intervention techniques for the prevention and treatment of IBD and colitis-associated colorectal cancer will be facilitated by the growth of this research area.